Предмет: Алгебра,
автор: dimassemenuta92dimas
Упростите выражение (x+2)(x-4)+2(x+3) и найти его значение при x= -5
Ответы
Автор ответа:
0
z=23
Автор ответа:
0
(Х+2)(х-4)+2(х+3)
х^2-4х+2х-8+2х+6
х^2+0-2
х^2-2
-5^2-2= -25-2=-27
Вроде все правильно)
х^2-4х+2х-8+2х+6
х^2+0-2
х^2-2
-5^2-2= -25-2=-27
Вроде все правильно)
Похожие вопросы
Предмет: Українська мова,
автор: uugghki
Предмет: Математика,
автор: Andersonfo
Предмет: Алгебра,
автор: dimabos2007
Предмет: Литература,
автор: smakov986
Предмет: Алгебра,
автор: гульжан4